Analysis of User Acceptance of the SATUSEHAT Application using the Extended UTAUT 2 Model - Ari Heriyadi; Apriansyah Putra; Rizka Dhini Kurnia; Putri Eka Sevtiyuni (Universitas Islam Indragiri, 2026)
The advancement of information technology in the healthcare sector has encouraged the Indonesian government to introduce the SATUSEHAT application as an integrated digital health platform. User acceptance of the SATUSEHAT application is influenced by various factors, including perceived usefulness, ease of use, trust, and privacy protection. This study aims to investigate the factors influencing user acceptance of the SATUSEHAT application using an Extended UTAUT2 model by incorporating Trust and Perceived Privacy as additional constructs. A quantitative research approach was employed by distributing an online questionnaire to SATUSEHAT users, and the collected data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The results indicate that Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Habit, Trust, and Perceived Privacy have positive and significant effects on Behavioral Intention. Furthermore, Facilitating Conditions, Habit, and Behavioral Intention were found to have positive and significant effects on Use Behavior. In contrast, Price Value was not found to have a significant influence on users' Behavioral Intention. These empirical findings confirm the explanatory capability of the Extended UTAUT2 model in understanding user acceptance of digital health technology. The results further suggest that the adoption of the SATUSEHAT platform is driven primarily by perceived usefulness, ease of use, social support, habitual use, trust, and confidence in data privacy protection, rather than by economic cost considerations.